Peranan Guru Bimbingan dan Konseling (BK) dalam Pemberian Layanan Informasi untuk Mengembangkan Perilaku Jujur Siswa - Nurul Liza; Sri Wahyuni (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2023)
This study aims to describe the role of guidance and counseling teachers (BK) in providing information services to develop honest behavior of students at SMP 6 Percut Sei Tuan. This research uses a type of qualitative research that is descriptive. Data collection techniques are observation, interviews, and documentation. The data used in this study is primary data. The object in this study was 9 junior high school students grade VII. This research data analysis technique uses data analysis techniques developed by Miles and Huberman. Analysis in this model consists of data reduction, display data, and conclusion/verification. Data validity techniques are through source triangulation, data collection technique triangulation, time triangulation. The results in this study are 1). The application of information services provided to the nine students was quite effective because students could understand how to instill an honest attitude to themselves. 2). The role of guidance and counseling teachers (BK) in responding to dishonest behavior is to provide information services containing material about the value of an attitude of honesty assisted by media infocus and lectures. 3). The factors found from honest behavior in junior high school were 9 respondents who experienced problems with honesty such as cheating. The reasons given were that students reasoned that the exam time was too short, lack of interest in studying, underestimated lessons and exams, habitually cheated, and lacked confidence in their own answers